Nilai Moral dalam Novel Dhalang Mbarang Katresnan Karya Tulus Setiyadi - Sulasmi, Sulasmi; Zaidah, Nuning; Werdiningsih, Yuli Kurniati (Universitas PGRI Semarang, 2022)
This study aims to describe the moral values depicted in the novel Dhalang Mbarang Katresnan by Tulus Setiyadi in terms of the sociology of literature study. The method used to describe moral values is descriptive qualitative. Data and research data sources are words, phrases and sentences in the novel Dhalang Mbarang Katresnan by Tulus Setiyadi. The data collection techniques used in this study were library techniques, note-taking techniques, and translation techniques. Based on the results of the analysis, it shows that the moral values in the novel Dhalang Mbarang Katresnan by Tulus Setiyadi are in the form of good moral values which include honesty, longing, principles, sincerity, cooperation, family: parent-child, husband-wife, and help; as well as bad moral values including regret